Isenzo senkulumo yokwenqaba ezimweni zemfundo yesiZulu - Ndlovu, Nompumelelo Priscilla (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MA (African Languages))--University of Stellenbosch, 2005.